A Neurotrophic Mechanism Directs Sensory Nerve Transit in Cranial Bone - Carolyn A. Meyers; Seungyong Lee; Takashi Sono; Jiajia Xu; Stefano Negri; Ye Tian; Yiyun Wang; Zhu Li; Sarah Miller; Leslie Chang; Yongxing Gao; Liliana Minichiello; et al. (Cell Reports, 2020)
Summary: The flat bones of the skull are densely innervated during development, but little is known regarding their role during repair. We describe a neurotrophic mechanism that directs sensory nerve transit in the mouse calvaria. Patent cranial suture mesenchyme represents an NGF (nerve growth factor)-rich domain, in which sensory nerves transit. Experimental calvarial injury upregulates Ngf in an IL-1β/TNF-α-rich defect niche, with consequent axonal ingrowth. In calvarial osteoblasts, IL-1β and TNF-α stimulate Ngf and downstream NF-κB signaling. Locoregional deletion of Ngf delays defect site re-innervation and blunted repair. Genetic disruption of Ngf among LysM-expressing macrophages phenocopies these observations, whereas conditional knockout of Ngf among Pdgfra-expressing cells does not. Finally, inhibition of TrkA catalytic activity similarly delays re-innervation and repair. These results demonstrate an essential role of NGF-TrkA signaling in bone healing and implicate macrophage-derived NGF-induced ingrowth of skeletal sensory nerves as an important mediator of this repair.